Speculations from 1850: being some thoughts on Rangiātea and the House of Tāmihana Te Rauparaha - Wood, Peter (Architectural History Aotearoa, 2012)
In March, 1852, the Wellington Independent reported its satisfaction at the sight of a drawing of the interior of Otaki Church, by Mr. C. D. Barraud. It declared the drawing a faithful representation of the church and its congregation that had been executed with "that taste and excellence we are led to expect from the pencil of so able an artist" ('[Untitled]" p 3). It concluded that the print would soon to be published - "in colours" – as it would make a beautiful, interesting and "novel" picture. This claim was added to a few days later in the New Zealand Spectator and Cook's Strait Guardian. Without irony they described the theologically themed depiction as being "spirited" as well as graphic. They go on to claim the "Native Church at Otaki" as one of the "lions" of the "settlement". Yet, for all that initial eagerness, Rangiātea would not go on to become a popular destination, and it has remained largely a picture of architecture. Indeed, even scholarly interest in it as an object of architecture does not appear in depth until the doctoral research of Sarah Treadwell, in the 1990s, who located the architectural significance of Rangiātea in a dialogue with the spatial and cultural patterns of the traditional Māori meeting house. In 2008 Treadwell reflected upon her PhD work with the admission that, in hindsight, her argument suffered the same kind of representational stability we can find in Barraud's rendition. The significance of Rangiātea as the singularly outstanding example of Māori building of the 1850s is uncontested, but Treadwell suggests that what we know and mean by historic "significance" – in his case history's preference for clear lines of origin and influence – are not to be depended upon as a stable discourse. I take that as an invitation to speculate on aspects of Rangiātea's influence and significance with a particular focus on a near neighbour in Ōtaki, the house of Tāmihana Te Rauparaha.